JUTSUONYM: INDEXICAL ALIGNMENT IN THE NAMING OF JUTSU IN COMIC, ANIMATION, AND VIDEO GAME SERIES - Sartika, Yustin; Widyarini Susilo Putri; Lilik Untari; Arianto, Puput; Muhammad Nur Kholis (UIN Raden Mas Said Surakarta, 2023)
Studies on charactonym leave an underinvestigated field of moves or jutsu in Japanese. Characters in action comics, anime, and computer games are equipped with moves e.g. Goku with his iconic Kamehameha, Monkey D. Luffy with his Gomu Gomu no Pistol, and Spider Man with his Maximum Spider. We argue that these moves deserve their own umbrella in charactonym studies – we call it jutsunym. Though adopting a Japanese martial art term, jutsunym is not limited on Japanese media. Investigating a corpus of jutsu defining comic, anime, and game series through the lens of Smith’s Peircean names as signs and Rudnyckyj’s relevance of content and form which was later developed by Gerus-Tarnawecky’s theory in literary onomastics, we found that in naming a jutsu or a move, the authors tend to consider what we call as indexical alignment – an alignment between the names of the jutsu or the moves with narrative, mechanical, visual, and audial elements. Narrative elements align themselves with jutsu names through story and character, mechanical elements through connotative and denotative, visual elements through indicative and implicative, and audial elements through quoting and catchphrasing.